2013
DOI: 10.1155/2013/874212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Accuracy of theMSLNGene Products, Mesothelin and Megakaryocyte Potentiating Factor, as Biomarkers for Mesothelioma in Pleural Effusions and Serum

Abstract: The MSLN gene products, soluble mesothelin and megakaryocyte potentiating factor (MPF), are being investigated as biomarkers for the asbestos-related cancer malignant mesothelioma (MM). Pleural fluid biomarkers of MM can be elevated when serum levels remain normal. The aim of this study was to determine if this was true for MPF and to compare levels of mesothelin. Biomarker concentrations were compared in 66 MM patients, 39 patients with other malignancies, 37 with benign disease, 18 asbestos-exposed healthy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Serum soluble mesothelin related peptides (SMRPs) levels have been proposed for the differentiation of MPM patients from patients with pleural metastases of different types of carcinomas (18,19). The diagnostic accuracy of mesothelin has been evaluated in several studies (21,(23)(24)(25) and the systematic review and meta-analysis recently performed showed a high specificity (around 89% and 96%) but a low sensitivity (between 32% and 47%) of mesothelin as a diagnostic marker; thus although SMRPs may help to discriminate the MPM from the non-MPM subjects, the sensitivity of the assay is still inadequate (88). In order to better characterize the sensitivity and specificity of SMRP as a biomarker for MPM it should take in consideration that SMRP performance as diagnostic biomarker could be influenced by genetics variants, as show in the recent work by De Santi et al (30) and SNP located in the promoter or in the 3'UTR of MSLN gene could affect protein expression levels (89).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%
“…Serum soluble mesothelin related peptides (SMRPs) levels have been proposed for the differentiation of MPM patients from patients with pleural metastases of different types of carcinomas (18,19). The diagnostic accuracy of mesothelin has been evaluated in several studies (21,(23)(24)(25) and the systematic review and meta-analysis recently performed showed a high specificity (around 89% and 96%) but a low sensitivity (between 32% and 47%) of mesothelin as a diagnostic marker; thus although SMRPs may help to discriminate the MPM from the non-MPM subjects, the sensitivity of the assay is still inadequate (88). In order to better characterize the sensitivity and specificity of SMRP as a biomarker for MPM it should take in consideration that SMRP performance as diagnostic biomarker could be influenced by genetics variants, as show in the recent work by De Santi et al (30) and SNP located in the promoter or in the 3'UTR of MSLN gene could affect protein expression levels (89).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%
“…After further processing, the SMRPs is released from the cell, and this is the most studied and so far the only Food and Drug Administration (FDA)-approved biomarker for MM (31,32). Mesothelin is expressed at low levels in normal mesothelial cells and is undetectable in most normal tissues.…”
Section: Soluble Mesothelin-related Peptides (Smrps)mentioning
confidence: 99%
“…MPF is a 31-kDa secreted cytokine, which derives from the cleavage of mesothelin, similarly to SMRPs (31). Like SMRPs, MPF was evaluated by ELISA in serum samples from MM patients and different control subjects.…”
Section: Mpfmentioning
confidence: 99%
“…The value below the limit of detection (LOD) was reported as 0.3 nM for statistic purpose in that the LOD for SMRP assay is 0.3 nM [5,7,9].…”
Section: Smrp Analysismentioning
confidence: 99%
“…Accumulating evidence indicate that SMRP is a candidate molecule investigated in health surveillance of workers exposed to asbestos, and is considered as a promising biomarker useful for early diagnosis and monitoring the progress of ARDs [4][5][6][7]. Given the high falsepositive of SMRP in a large-scale prospective study of SMRP for screening for ARDs in asbestos-exposed individuals [8], it is imperative to investigate the potential factors influencing the SMRP concentrations in subjects with a history of asbestos exposure.…”
Section: Introductionmentioning
confidence: 99%